Urgensi Pendidikan Seksual Anak: Perspektif Al-Qur’an dan Eksplorasi Preventif - Nur Ibad, Taqwa; Sari, Rita; Wahidah, Finadatul (Diksi: Jurnal Pendidikan dan Literasi, 2024)
This research highlights the urgency of sexual education from the perspective of the Qur'an and the preventive exploration by the community towards sexual problems in children. The purpose of this study is to analyze the views of the Qur'an and preventive efforts from the community toward sexual education for children. The research method used is a phenomenological study. The results of the study reveal that sexual education is important to be delivered to children, with material that is appropriate to their age and stage of development. This education must not deviate from the guidance of the Qur'an and must be in harmony with human values and lifelines. The Qur'an teaches sex education through certain verses that emphasize ethical, moral, and moral aspects of sexual behavior